Resilience as a Mediator of the Association Between Perceived Stigma and Quality of Life Among People With Inflammatory Bowel Disease - Luo, Dan; Zhou, Meijing; Sun, Lifu; Lin, Zheng; Bian, Qiugui; Liu, Meihong; Ren, Shurong (Frontiers in Psychiatry, 2021)
Background: Improving Quality of Life (QOL) is an essential objective in the management of inflammatory bowel disease. An accumulating body of research has been conducted to explore the association between perceived stigma and QOL among patients with chronic illness. Still, underlying mechanisms behind this pathway have not been thoroughly examined. Objective: To investigate (a) the effect of perceived stigma on QOL among patients with inflammatory bowel disease; and (b) the mediating role of resilience in the association between perceived stigma and QOL. Methods: This cross-sectional study included a convenient sample of patients diagnosed with inflammatory bowel disease from four tertiary hospitals in Jiangsu Province, China. Patients completed the Perceived Stigma Scale in Inflammatory Bowel Disease (PSS-IBD), the Resilience Scale for Patients with Inflammatory Bowel Disease (RS-IBD), and the Inflammatory Bowel Disease Questionnaire (IBDQ). A bootstrapping analysis was implemented using the SPSS macro PROCESS. Results: A total of 311 patients with Cohn’s disease and ulcerative colitis participated in this study, and 57.6% were men. The mean disease duration was 3.51 ± 1.04 years. Approximately 40% of the sample exceeded the criterion score for moderate stigma. Patients who perceived moderate or severe stigma reported lower QOL compared with those with mild stigma. After controlling for sociodemographic and clinical variables, we observed that perceived stigma was negatively associated with resilience. Moreover, resilience was found to mediate the relationship between perceived stigma and all aspects of QOL. Conclusions: These findings suggested that QOL of patients with inflammatory bowel disease was associated with perceived stigma and resilience and identified the mediating effects of resilience in the relationship between perceived stigma and QOL. Furthermore, this suggests that integrating intervention techniques to target resilience into the QOL improvement program of individuals with perceived stigma is possible.